Hepatic Epithelioid Hemangioendothelioma and the Danger of Misdiagnosis: Report of a Case. (28th February 2013) - Neofytou, Kyriakos; Chrysochos, Andreas; Charalambous, Nikolas; Dietis, Menelaos; Petridis, Christos; Andreou, Charalampos; Petrou, Athanasios
Abstract : Malignant hepatic epithelioid hemangioendothelioma (HEHE) is a rare malignant tumor of vascular origin. Nonspecific symptoms and the absence of experience of surgeons, radiologists, and histopathologists due to the rarity of HEHE make the diagnosis of this entity very challenging. Misdiagnosis is not a rare event, and the consequences of such an event are catastrophic. We report a case of a patient suffering from HEHE in which the initial diagnosis was hepatocellular carcinoma (HCC). The presence of normal laboratory values, liver function tests, tumor markers along with the absence of a chronic liver disease, or any other predisposing factors for HCC, was in contrast with the diagnosis of HCC. Clinical suspicion drove us to the repetition of a liver biopsy and the reevaluation of the sample by a more experience histopathology department in liver tumors. The last biopsy confirmed the diagnosis of HEHE, and the patient escaped any unnecessary treatment for a nonexisting HCC.